THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT PAMAPERSADA NUSANTARA - Dedi Suharyadi; Rini Martiwi; Instianti Elyana; Aan Rahman; Nyoman Suardhita (Jurnal Ekonomi, 2023)
This research aims to determine the influence of organizational culture and work environment on employee performance at PT Pamapersada Nusantara, both partially and simultaneously. This research uses a quantitative descriptive method by distributing questionnaires to PT Pamapersada Nusantara General Service Division employees. The population in this study was 70 people at PT Pamapersada Nusantara General Service Division. Meanwhile, the number of samples was 70 people, and the sampling technique used was the Purposive Sampling technique. In analyzing the research data, SPSS 26 was used to calculate the results of the Multiple Linear Regression variable test, t-test, F test, and determination analysis. Based on the t-test, this research shows that organizational culture and work environment positively and significantly affect employee performance at PT Pamapersada Nusantara General Service Division. Based on the results of the F Test, corporate culture and the work environment have a positive and significant effect on employee performance at PT Pamapersada Nusantara General Service Division. Based on the results of multiple regression analysis, the influence of organizational culture and work environment on employee performance at PT Pamapersada Nusantara General Service Division is 76.5%. In comparison, the remaining 23.5% is influenced by other variables not examined in this research.